2021
DOI: 10.1088/1755-1315/743/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Potential of fibrinolytic protease enzyme from tissue of sand sea cucumber (Holothuria scabra) as thrombolysis agent

Abstract: Cardiovascular diseases (CVD) are still the main cause of death in modern society with thrombosis as their most common underlying pathology. The occurrence of thrombosis is characterized by thrombus formation in the circulatory system of the body causing blood clot blockage. Thrombus blocking blood vessels can be destroyed through fibrinolysis by plasmin. Commonly administered fibrinolytic drugs activate plasminogen and convert plasminogen to plasmin which degrades fibrin. However, these agents have limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…thuringiensis HSFI-12 Anticoagulant activity assay was carried out by comparing clotting times of the positive control of blood with 10% EDTA solution, negative control of blood with no treatment (as an arti cial thrombus), and samples of blood with treatments of crude and dialysate protease added in various volume variations. The use of this negative control as a thrombus model was previously reported by Hidayati et al (2021a) and Fuad et al (2021) Visual appearances of anticoagulation performance of both crude and dialysate proteases along with controls were displayed in Figure 4. The measured blood clotting time (CT) is displayed in Table 2.…”
Section: Anticoagulant Activity Test Of Protease From Bacillusmentioning
confidence: 82%
See 2 more Smart Citations
“…thuringiensis HSFI-12 Anticoagulant activity assay was carried out by comparing clotting times of the positive control of blood with 10% EDTA solution, negative control of blood with no treatment (as an arti cial thrombus), and samples of blood with treatments of crude and dialysate protease added in various volume variations. The use of this negative control as a thrombus model was previously reported by Hidayati et al (2021a) and Fuad et al (2021) Visual appearances of anticoagulation performance of both crude and dialysate proteases along with controls were displayed in Figure 4. The measured blood clotting time (CT) is displayed in Table 2.…”
Section: Anticoagulant Activity Test Of Protease From Bacillusmentioning
confidence: 82%
“…The bacterial protease, however, did not show direct brinolytic activities. It was proven by the fact that the bacterial protease was unable to utilize brin as a substrate (Hidayati et al, 2021a;Hidayati et al, 2021b). This shows that the thrombolysis activ- ity of protease of strain HSFI-12 likely comes as a plasminogen activator (PA), which action will activate plasmin leading to the cleavage of brins (Akhtar et al, 2017) .…”
Section: Determination Of Molecular Weight and Speci City Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Plasmin acts in the breakdown of fibrin in blood clots, but when plasmin cannot work normally, enzymatic thrombolytic agent therapy is required. [9][10][11] Commercial thrombolytic agents such as tissue plasminogen activators (tPAs), urokinase (UK), streptokinase (Sk) and nattokinase (Nk) have the disadvantages of causing gastrointestinal bleeding and allergic reactions, are expensive, low specificity and also has short half-life. Therefore, it is necessary to develop new thrombolytic agents.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…Thrombolytic agents can be protease enzymes, which is known to be safe to use, one of which produce by Bacillus spp isolated from fermented products of the digestive organs of sea cucumbers (Holothuria scabra). 9 The protease produced by the strain of Bacillus spp HSFI-12 was then partially purified through ammonium sulphate precipitation followed by dialysis. It was found that in vitro blood lysis activity of the dialysate protease of strain Bacillus spp HSFI-12 was higher than its crude protease and the activity was higher than the commercial Nk as a positive control.…”
Section: Enzyme Productionmentioning
confidence: 99%